Oral language and phonological awareness. Empirical study on a sample of preschool district Ventanilla–Callao - Rodríguez Melgar, Silvia (2015)
Non-experimental, transversal, descriptive correlational design research. Carried out in a sample of 30 boys and girls of 5 years of age from a state educational institution in the district of Ventanilla, Callao,Peru. The variables oral language and levels of phonological awareness were analyzed. For the purposes of data collection, the Oral Language Assessment - Ramos ELO, Cuadrado and Fernández (2008) and the Metalinguistic Skills Test - THM by Gómez, Valero, Buadas and Pérez (1995) were used. The results reveal significant high correlation in oral language and phonological awareness levels. In turn, there was a strong correlation between the syntactic aspect of oral language and phonological awareness in the first place, consecutively, between the semantic component and phonological awareness. Auditory discrimination was the least correlated in all the analyzes.